2016
DOI: 10.1681/asn.2015080896
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopodin Limits TRPC6 Podocyte Surface Expression and Attenuates Proteinuria

Abstract: Gain-of-function mutations of classic transient receptor potential channel 6 (TRPC6) were identified in familial FSGS, and increased expression of wild-type TRPC6 in glomeruli is observed in several human acquired proteinuric diseases. Synaptopodin, an actin binding protein that is important in maintaining podocyte function, is downregulated in various glomerular diseases. Here, we investigated whether synaptopodin maintains podocyte function by regulating podocyte surface expression and activity of TRPC6. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…For example, cGMP accumulation has been linked to podocyte contractility, mobility, and cytoskeletal structure 7 ; PKG-1 is associated with poor clinical outcome in renal cell carcinoma 8 ; PPAR-g agonists have been shown to protect podocytes from nephropathies 9 ; and overexpression of TRPC6 alone is sufficient to cause podocyte damage and subsequent glomerulopathies. 10,11 Collectively, these findings highlight the importance of crosstalk among cGMP, PKG-1, PPAR-g, and TRPC6, and demonstrate the importance of TRPC6 signaling in kidney disease.…”
mentioning
confidence: 72%
“…For example, cGMP accumulation has been linked to podocyte contractility, mobility, and cytoskeletal structure 7 ; PKG-1 is associated with poor clinical outcome in renal cell carcinoma 8 ; PPAR-g agonists have been shown to protect podocytes from nephropathies 9 ; and overexpression of TRPC6 alone is sufficient to cause podocyte damage and subsequent glomerulopathies. 10,11 Collectively, these findings highlight the importance of crosstalk among cGMP, PKG-1, PPAR-g, and TRPC6, and demonstrate the importance of TRPC6 signaling in kidney disease.…”
mentioning
confidence: 72%
“…A large number of studies have revealed that EGCG could inhibit the expression of HIF-1α [9,10]. HIF-1α is highly related with ROS production and cell apoptosis [34,35]. Over-expression of HIF-1α promotes fibrosis and contributes to CKD [13].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of HIF-1α promotes fibrosis and contributes to CKD [13]. Prolonged activation of HIF-1α in kidney could lead to further tissue destruction [36] and blockade of HIF-1α may play a protective role in FSGS [34]. Importantly, it also has been reported that EGCG inhibit ROS production and cell apoptosis by inhibiting the expression of HIF-1α [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRPC6-induced calcineurin activation affects numerous downstream signaling pathways that may contribute to disease progression in CKD. For example, the podocyte protein synaptopodin associates with the actin cytoskeleton and plays a key role in maintaining the complex morphology of the glomerular podocyte, as well as inhibiting cell surface expression of TRPC6 [87]. As shown in Figure 3, Faul et al [88] found that synaptopodin was phosphorylated by either protein kinase A (PKA) or calcium-dependent protein kinase II (CaMKII).…”
Section: Trpc Family Members In Glomerular Diseases: Mechanisms Of Rementioning
confidence: 99%